MAGNETIC SUSCEPTIBILITY OF THE SOUTHERN CHERNOZEMS OF UKRAINE, CASE STUDY FROM ODESSA REGION - Menshov, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Soil studies are an important component of the present geological and geophysical studies to solve fundamental and applied problems. According to the new Law on Higher Education different fields of research were combined into the Earth Sciences in conformity with the international classification. The integrated approach for investigations in geology, geography, soil science, geophysics is an extremely urgent task now. We studied an area on the Black Sea coast, in the coastal part of the Odessa region, near the Sanzheyka steppe area, which was not subjected to agricultural processing. Landscape conditions are the flat part with the high precipice near the seashore. The soils of this area are classified as southern chernozems (Haplic Chernozems in WRB classification). The methods used include reconnaissance soil science research, bulk magnetic susceptibility measurements in the field, soil sampling for the laboratory analysis. In the magnetometric laboratory we measured mass specific magnetic susceptibility χ, the frequency dependence of the magnetic susceptibility χfd. The results showed that the magnetic susceptibility of the upper humus horizon A is 80-100×10-8 m3/kg. The compacted soil of the field roads presented χ=130-180×10-8 m3/kg. At the same time the clay roads with eroded soil are characterized by the values of χ=50-70×10-8 m3/kg. This indicates the replacement of the upper humus horizon by transitional horizon B. This confirms the soil erosion processes, which in turn is proved by the magnetic susceptibility study of soil horizons within the soil profile. The transitional horizon B was identified at a depth of 40-70 cm with magnetic susceptibility 70-80×10-8 m3/kg. The underlying bedrocks C started from the 80 cm with χ=30-40×10-8 m3/kg. The southern chernozems are one of the most magnetic soils in Ukraine. The topsoil of the Ukraine chernozem contains fine-grained oxidized magnetite and maghemite of pedogenic origin. The frequency dependence of the magnetic susceptibility χfd is 4-10%. This indicates the presence of superparamagnetic grains among the magnetic materials in the soils. Pedogenesis predominates in the studied soils. Soil pollution wasn't identified. Southen chernozems are extremely magnetic and should be investigated during magnetic surveys and environmental monitoring to develop an optimal cost-based methodology and enhance the uniqueness of the interpretation of the results. For example, we identified the area with high erosion risks. This clay road is allocated by the contrast magnetic signal. The detailed information on magnetic minerals, grain size and stability, areal distribution of the magnetic susceptibility should be involved for a more accurate interpretation of the obtained soil magnetic parameters data to assess soil erosion. We need to combine the magnetic methods with agronomic risk assessment of erosion processes within the productive lands.
Keywords: magnetic susceptibility; soil magnetism; soil erosion; southern chernozems; Haplic Chernozems